Comparison studies of typing and handwriting in Chinese language learning: A synthetic review. (2021) - Lyu, Boning; Lai, Chun; Lin, Chin-Hsi; Gong, Yang
Highlights: The effects of typing and handwriting manifest differently in English and Chinese. Handwriting and typing activate different aspects of Chinese character processing. The effects of typing and handwriting on writing performance are mixed. Abstract: The differential effects of typing and handwriting on language performance have attracted much research attention, including literature reviews and meta-analyses in the field of English-language education. However, how these two modes of language production interact with the unique characteristics of Chinese characters and the various dimensions of Chinese language learning and performance remains an open question. The present study therefore presents a synthetic review of empirical studies examining the effects of typing and handwriting on Chinese language performance. The study found that typing has a greater effect on Chinese learners' phonology recognition and phonology-orthography mapping than handwriting, and this advantage was more salient in Chinese than in English. Unlike in English, where it only benefited orthographic recognition of letters, handwriting had positive effects on Chinese learners' orthography recognition and orthography-semantic mapping at both the character and lexical levels. Moreover, in contrast with consistent findings concerning the positive effect of typing on English writing performance, the effects of typing on Chinese writing performance were mixed. The findings suggest that the effects of typing and handwriting might manifest differently in the two languages, calling for differential theorization of the cognitive impact of typing on English and Chinese language processing.